2014
DOI: 10.2135/cropsci2013.09.0616
|View full text |Cite
|
Sign up to set email alerts
|

Biotype Differences for Resistance to Russian Wheat Aphid in Barley

Abstract: Russian wheat aphid [RWA; Diuraphis noxia (Mordvilko)] is a worldwide insect pest of barley (Hordeum vulgare L.), causing crop losses each year. Previously identified resistant barley lines do not show variable reactions to the eight United States RWA biotypes identified by wheat reactions. However, additional RWA isolates have been identified outside the United States. The objective of this research was to determine whether additional RWA biotypes that impact resistance in barley exist and whether resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
2
7
2
Order By: Relevance
“…The 1H and 3H haplotypes confirmed QTL identified in previous AM and biparental studies (Mittal et al, 2008(Mittal et al, , 2009Dahleen et al, 2012Dahleen et al, , 2014. The 1H and 3H haplotypes confirmed QTL identified in previous AM and biparental studies (Mittal et al, 2008(Mittal et al, , 2009Dahleen et al, 2012Dahleen et al, , 2014.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The 1H and 3H haplotypes confirmed QTL identified in previous AM and biparental studies (Mittal et al, 2008(Mittal et al, , 2009Dahleen et al, 2012Dahleen et al, , 2014. The 1H and 3H haplotypes confirmed QTL identified in previous AM and biparental studies (Mittal et al, 2008(Mittal et al, , 2009Dahleen et al, 2012Dahleen et al, , 2014.…”
Section: Discussionsupporting
confidence: 87%
“…They reported high heritability for resistance (77.5-88.7%). Surprisingly, they reported that almost all R lines showed the same marker profile, a result inconsistent with a subsequent study that showed variable responses to several RWA biotypes among lines identical with respect to their marker profile (Dahleen et al, 2014). Surprisingly, they reported that almost all R lines showed the same marker profile, a result inconsistent with a subsequent study that showed variable responses to several RWA biotypes among lines identical with respect to their marker profile (Dahleen et al, 2014).…”
Section: Genetic Diversity For Russian Wheat Aphid Resistance As Detecontrasting
confidence: 59%
See 3 more Smart Citations